Improving Student Learning Outcomes with the Application of Pendidikan Matematika Realistik Indonesia (PMRI) - Indah Silvana Aprilia; Nur Awalia (Indo-MathEdu Intellectuals Journal, 2020)
Pendidikan Matematika Realistik Indonesia (PMRI) is a learning tool that places students as subjects in learning and the learning process uses real-world contexts as a medium in their learning so as to help students understand the material being studied. The purpose of this study is to determine the application of PMRI in the learning process to improve student learning outcomes in the Social Arithmetic material of students VII of SMP Amanah Bangsa. This research was conducted using Classroom Action Research, which is a study that aims to determine the improvement of student learning outcomes. The subjects used in the study were 30 people, namely the number of all grade VII students at SMP Amanah Bangsa. The instruments used are observation and test. After carrying out the research and going through the data analysis process, the results of the analysis showed that there was an increase in student learning outcomes with the application of PMRI, namely in the initial test obtained an average score of 44.00 with a percentage of completion of 23.33%, increased in cycle I to 64.00 with a percentage of completion of 56.67% and increased significantly in cycle II to 79.00 with a percentage of completion of 83.33%.